Seropositivity for Bovine Viral Diarrhea and Enzootic Bovine Leukemia viruses in Blanco Orejinegro cattle in Colombia and infection associated-factors - A. Saldarriaga-Saldarriaga; M. Londoño-Gil; L. G. González-Herrera; J. C. Rincón-Flórez; A. López-Herrera (Revista de la Facultad de Medicina Veterinaria y de Zootecnia)
Serological controls for diseases of viral origin in animal production systems and the identification of factors associated with infections are decisive elements to establish prevention and control measures. The aim of this study was to establish the serological status for Bovine Viral Diarrhea (BVD) and Enzootic Bovine Leukemia (EBL) viruses in Blanco Orejinegro (BON) cattle from Colombia, and to identify the factors associated with seropositivity. A cross-sectional study was conducted with a total of 498 animals of all age groups and physiological states of the BON breed were selected, belonging to 14 herds located in 6 states of Colombia, in which a survey with 27 questions was conducted. By means of the chi-square test, possible factors associated with seropositivity against the 2 viruses were identified. A sample of 4 ml of blood was taken from each animal to extract plasma and make indirect Elisa tests to detect antibodies against both pathogens. General seropositivity of 27,1% was obtained for EBL, finding as factors associated with seropositivity the inadequate disposition of placental tissues after delivery of the cows and the non-performance of serological tests on new animals entering the herd. For BVD, seropositivity obtained was 50,6%, and the factors associated with seropositivity identified were having had a history of the disease in the herd, and using semen from bulls that are not known to be free for the infection. We suggest establishing control measures considering the factors associated with each viral infection to limit their expansion in the BON cattle production systems of Colombia.